SOME RESULTS ON HOLOMORPHIC FUNCTIONS BASED ON ERROR FUNCTION - Sailaja Peesapati,; N. Sri Lakshmi Sudha Rani,; P.Thirupathi Reddy, (Utilitas Mathematica, 2025)
In this paper, we introduce a new subclass of uniformly convex functions with negative coefficients defined by error function. We obtain the coefficient bounds, growth distortion properties, extreme points and radii of close-to-convexity and starlikeness for functions belonging to the class ????????(????, ????). Furthermore, we obtained modified Hardamard product, convolution and integral operators for this class.